Jardin ou forêt d’après Nature, comment cultiver son rapport au monde: le cas des Echez d’Amours et du Livre des Echez amoureux moralisés - Deleville, Prunelle (Studia Romanica Posnaniensia, 2025)
How can one follow the path of nature within a space shaped by culture? This is the question posed by the 14th-century Echecs amoureux, which describes two antagonistic vegetal spaces: on the one hand, the wild forest of Diana, which corresponds to the reasonable way of being in the world; on the other, the delectable garden of Venus, which leads along the path of sensuality. This initial boundary proves surprising. Culture (the garden) is not, as you might expect, on the side of reason, while the forest leads to it. The complexity of this relationship is confirmed in the illuminations, which combine contradictory plant elements to represent these spaces. These plays on ambiguity suggest that the forest and the garden have something in common in that they remain illusory: Diana’s primitive forest is a-topic, belonging to the past, while Venus’s beautiful garden is deceptive. The ambiguity of our relationship with plants is a way of questioning man’s place in the world. The text suggests that we cannot follow just one path or the other, but that a happy medium seems necessary. The solution that Echecs amoureux seems to propose lies in a world that combines the plant and the urban, subsumed – quite unexpectedly for a modern reader – by the urban.